Determinan Tingkat Pengangguran di Negara-Negara Organisasi Kerjasama Islam (OKI) dan Negara-Negara Non OKI di Asia Tenggara Periode Tahun 1985-2014 (Indonesia, Malaysia, Thailand, Singapura, dan Filipina) - Abdul Haris Masi; Raditya Sukmana (Universitas Airlangga, 2017)
In freetrade, country has to maximize the human resources in order to have quality skills which can compete, so unemployment must be avoid. OIC starts to have concern on this problem. In 2015, OIC held conference in Jakarta which discussed the solution to overcome youth unemployment. This research uses data by the World Bank and Central Agency on Statistics of Indonesia with quantitative approach. The data were analyzed by using panel data analysis. The inflation rate significantly affects the decreasing of the unemployment rate in the Non OIC countries, but does not significantly affect the unemployment rate in the OIC countries. GDP significantly affects the decreasing of the unemployment rate both in the OIC countries and the Non OIC countries. Population significantly affects the increasing of the unemployment rate in The OIC countries and does not significantly affect the unemployment rate in the Non OIC countries.